2011
DOI: 10.1007/s10344-011-0505-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites in the endangered Fennoscandian population of arctic foxes (Vulpes lagopus)

Abstract: The Fennoscandian arctic fox (Vulpes lagopus) population is endangered due to overharvest and competition with the larger red fox (Vulpes vulpes). In this study, we have screened the population in Sweden for endoparasites by analysis of non-invasively faecal samples collected at reproductive dens during two summers, one with low food abundance (2008) and the other with high food abundance (2010). Eggs, larvae and oocysts of a total of 14 different endoparasites were identified with a species richness per inhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
(22 reference statements)
5
19
0
Order By: Relevance
“…Also prevalence rates of T. leonina reported from dogs of seve-ral countries of the Balkan peninsula were lower than those of T. canis (Olteanu, 2000;Papazahariadou et al, 2007) with the latest report on the rates of infection of 0.9 % and 75.7 %, respectively (Xhaxhiu et al, 2011). Research of Meijer et al (2011) on the endoparasites of arctic foxes (Vulpes lagopus) during two summers (2008 and 2010) showed the same pattern of nematode infection with T. leonina the most frequent parasite species found in 93 % and 65 % of the dens. In contrast, T. canis prevalence was considerably lower -7 % and 30 %.…”
Section: Abstract: T Canis; T Cati; Toxascaris Leonina; Carnivoresmentioning
confidence: 89%
“…Also prevalence rates of T. leonina reported from dogs of seve-ral countries of the Balkan peninsula were lower than those of T. canis (Olteanu, 2000;Papazahariadou et al, 2007) with the latest report on the rates of infection of 0.9 % and 75.7 %, respectively (Xhaxhiu et al, 2011). Research of Meijer et al (2011) on the endoparasites of arctic foxes (Vulpes lagopus) during two summers (2008 and 2010) showed the same pattern of nematode infection with T. leonina the most frequent parasite species found in 93 % and 65 % of the dens. In contrast, T. canis prevalence was considerably lower -7 % and 30 %.…”
Section: Abstract: T Canis; T Cati; Toxascaris Leonina; Carnivoresmentioning
confidence: 89%
“…So far, M. canislagopodis has only been reported in Iceland (Loos-Frank et al 1992;Skirnisson et al 1993). Representatives of the genus are well known from Scandinavia and have for example been reported from red fox and raccoon dog in Denmark (Saeed et al 2006;Al-Sabi et al 2013 and from arctic foxes in Sweden (Meijer et al 2011). In Greenland, Kapel and Nansen (1996) reported M. lineatus from arctic foxes, but these identifications have not been confirmed with molecular methods.…”
Section: Molecular Analysis-coi and 12s Domainsmentioning
confidence: 91%
“…In Greenland, Kapel and Nansen (1996) reported M. lineatus from arctic foxes, but these identifications have not been confirmed with molecular methods. Meijer et al (2011) erroneously reported M. canislagopodis from the arctic fox in Svalbard, citing Stien et al (2002), a reference on reindeer parasites, and not mentioning arctic fox parasites. This error was confirmed in an extensive study carried out on endoparasites of 353 arctic foxes from Svalbard where no Mesocestoides infections were recorded (Stien et al 2010).…”
Section: Molecular Analysis-coi and 12s Domainsmentioning
confidence: 92%
“…Otranto and Deplazes (45) note that Toxocara canis infections are generally higher in young foxes (under 6 months of age), although, a relatively high prevalence rate have also been among adult foxes in endemic territories, representing weak immune status against intestinal.Higher prevalence of Toxocara canis than Toxascaris leonina has also been found in other countries, including Denmark (59.4% and 0.6%) (40), Italy (52.6% and 0%)(27), Slovakia (25.8% and 17.5%)(46) and Kyrgyzstan (30.4% and 5.9%) (47). However, a higher prevalence of Toxascaris leonina than Toxocara canis has been found in some countries, including Sweden (respectively 65.0% and 30.0%)(39), Turkey (65.0% and 20.0%)(48), Greenland (41.8% and 0.0%)(49) and Norway (12.9% and 1.6%)(38). The exceptions are the studies from the Czech Republic, where the prevalence of both species in foxes was equal (2).The parasite with the lowest prevalence in this study was Trichuris vulpis.…”
mentioning
confidence: 97%
“…Toxocara canis and Toxascaris leonina were found to co-occur in only 14 foxes (J = 3.8%).This may indicate that these two species of parasites share an antagonistic relationship or are in competition with each other. The high prevalence of Toxocara canis among foxes and pets may lead to a low prevalence of Toxascaris leonina and vice versa(39). However, Jankovska et al (2) report the co-occurrence of these two nematode species 70.6% of tested foxes in Czech Republic.…”
mentioning
confidence: 99%